COVID‐19 infection in patients with intestinal failure: UK experience. Issue 6 (6th May 2021) - Allan, P. J.; Ambrose, T.; Mountford, C.; Bond, A.; Donnellan, C.; Boyle, R.; Calvert, C.; Cernat, E.; Clarke, E.; Cooper, S. C.; Donnelly, S.; Evans, B.; et al.
Abstract: Background: The direct effect of the coronavirus disease 2019 (COVID‐19) pandemic on patients with intestinal failure (IF) has not been described. Methods: We conducted a nationwide study of UK IF centers to evaluate the infection rates, presentations, and outcomes in patients with types 2 and 3 IF. Results: A total of 45 patients with IF contracted COVID‐19 between March and August 2020; this included 26 of 2191 (1.2%) home parenteral nutrition (HPN)–dependent adults and 19 of 298 (6.4%) adults hospitalized with type 2 IF. The proportion of patients receiving nursing care for HPN administration was higher in those with community‐acquired COVID‐19 (66.7%) than the proportion in the entire HPN cohort (26.1%; P < .01). Two HPN‐dependent and 1 hospitalized patient with type 2 IF died as a direct consequence of the virus (6.7% of 45 patients with types 2 or 3 infected). Conclusion: This is the first study to describe the outcomes of COVID‐19 in a large cohort of patients requiring long‐term PN. Methods to reduce hospital and community nosocomial spread would likely be beneficial.